Rolling back the gains: Maternal stress undermines pregnancy health after Flint's water switch - Danagoulian, Shooshan; Jenkins, Derek (Health economics, 2021)
Environmental disasters impact disadvantaged communities disproportionately both through the epidemiological challenge of exposure, but also by undermining the progress of public health efforts. This paper studies changes to smoking cessation, breastfeeding, and weight gain during pregnancy in the period following the switch in water supply in Flint, Michigan, in April 2014. As the switch resulted in immediate and significant deterioration in water quality, eventually leading to its contamination with lead, we estimate a 10.5 percentage point increase in smoking and a 2.1 percentage point decrease in breastfeeding. We show evidence that these changes in maternal behavior are linked to increased stress due to changing water quality. We estimate that the increase in smoking alone is responsible for most of the increase in incidence of low birthweight among infants in Flint, resulting in $700 additional costs per birth. Increased smoking during pregnancy and lower breastfeeding rates in Flint roll back years of public health efforts, resulting in lifetime higher rates of cardiovascular disease, diabetes, and cancer for mothers in the community.